Pelatihan Gamelan Sanggar Budaya Hamong Rasa Guna Meneruskan Generasi di Kabupaten Wonosobo - azizatullatifah, aisyah (Jurnal Dinamika Sosial Budaya, 2022)
Supporting music has the power to represent the culture of a person or group at a particular time. He understood to have a basis for understanding, determining the ways and actions in each note produced. The color of the voice, the pitch and the musical work in each region have many differences. Because in essence, music is a work of art that is here is an aesthetic symbol of every different cultural community.Gamelan is a musical instrument that represents or depicts Javanese culture. Some Javanese gamelan in Surakarta, Yogyakarta and Cirebon, among others are Kyai Guntur Madu, Kyai Guntur Sari, Kyai Naga Wilaga and Gong Sekati. This orchestra has a pentatonic scale in the slendro scale system and the pelog scale system. Each gamelan has an honorary name as it deserves a sacred heirloom. slendro on the gamelan used as the research sample. While the independent variables are the frequency and color of the sound of each chord.